CESTA BÁSICA PARA SUPRIR AS NECESSIDADES DE FAMÍLIAS CARENTES: UMA EXPERIÊNCIA COM A MODELAGEM MATEMÁTICA - Scorziello, Laís; Bueno, Fábio; Campos, Mylena; Mistura Zanon, Jéssica (LINKSCIENCEPLACE, 2026)
The objective of this article is to describe the first experience of future teachers of Mathematics with Modeling and, thus, it is a work developed during the discipline of Mathematical Modeling II, of the course of Degree in Mathematics. For this, the teacher of the discipline directed that the class was divided into groups and each one chose a theme to solve a problem from the modeling. Thus, we will relate our experience by investigating the theme "Basic basket to meet the needs of needy families," in which we set up a fictional ONG to raise funds and serve the families in need. Based on this theme, it was possible to develop a modeling project, following the steps described by Burack and Klüber in Considerations on Mathematical Modeling from a Mathematical Education perspective. As we authors of this work, we are graduates in Mathematics, with this activity, we were able to produce knowledge about this methodological procedure, positively adding in their teaching identities and feeling safer to, in the future, develop such methodologies in their classes.